4(x+2)-7=2x+2(-1+x)

Simple and best practice solution for 4(x+2)-7=2x+2(-1+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+2)-7=2x+2(-1+x) equation:


Simplifying
4(x + 2) + -7 = 2x + 2(-1 + x)

Reorder the terms:
4(2 + x) + -7 = 2x + 2(-1 + x)
(2 * 4 + x * 4) + -7 = 2x + 2(-1 + x)
(8 + 4x) + -7 = 2x + 2(-1 + x)

Reorder the terms:
8 + -7 + 4x = 2x + 2(-1 + x)

Combine like terms: 8 + -7 = 1
1 + 4x = 2x + 2(-1 + x)
1 + 4x = 2x + (-1 * 2 + x * 2)
1 + 4x = 2x + (-2 + 2x)

Reorder the terms:
1 + 4x = -2 + 2x + 2x

Combine like terms: 2x + 2x = 4x
1 + 4x = -2 + 4x

Add '-4x' to each side of the equation.
1 + 4x + -4x = -2 + 4x + -4x

Combine like terms: 4x + -4x = 0
1 + 0 = -2 + 4x + -4x
1 = -2 + 4x + -4x

Combine like terms: 4x + -4x = 0
1 = -2 + 0
1 = -2

Solving
1 = -2

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 11+8x-11-6x+6=11+(8x-11)-6x+6 | | 4(n-5)+15n=-4(-10n+3)-21n-8 | | 16=0 | | (x-3)x(x-5)= | | 5(3x-6)=9x-12 | | y-3=-3(x+3) | | y-3=-3(x-1) | | y+3=-3(x-3) | | k-16=-36 | | 4y+2=x | | -7t/2=7 | | y+3=-3(x+1) | | 3+2x-9=5x-21 | | 4xsquared+100=0 | | -3(5x+3)-2(x-6)= | | 1/2x2-3 | | c-79.9=-104.9 | | 3-3x=7x+12 | | w+6=57 | | 24v^4w^9-18vw^3y^5= | | 5x?5x= | | 693950=.798750X | | 693950=.798750 | | 8xy-9x= | | 400x+36000=2000x+12000 | | y=5/6(126) | | 5/6-1/3n=5p-2np | | 1-2x=6-4x | | 4X-2.5=7.4 | | 7b-16=-45 | | .08X=700 | | 7-(3n-8)=-6 |

Equations solver categories